1988
DOI: 10.1002/j.1460-2075.1988.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations in stem and loop regions on the structure and function of adenovirus VA RNAI.

Abstract: Adenovirus virus‐associated (VA) RNAI is required for efficient protein synthesis at late times of adenoviral infection, and in some other situations where double‐stranded RNA (dsRNA) is present. It prevents inhibition of protein synthesis by a dsRNA‐activated protein kinase and the secondary structure of VA RNAI is though to be important for its activity. To test this idea and to define structures and sequences responsible for VA RNAI activity, we constructed several mutant VA RNA genes and tested them in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
95
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 64 publications
3
95
0
Order By: Relevance
“…In contrast, the pH dependence is reversed for bp RNA, which lacks the (A⅐C) ϩ mismatch pair (Fig. 1). primary binding site and its complex central domain as the major determinant of inhibitory activity (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Although far less extensively examined, prior mutagenesis suggested that an intact terminal stem structure, particularly adjacent to the central domain, might also contribute to inhibition of PKR (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the pH dependence is reversed for bp RNA, which lacks the (A⅐C) ϩ mismatch pair (Fig. 1). primary binding site and its complex central domain as the major determinant of inhibitory activity (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Although far less extensively examined, prior mutagenesis suggested that an intact terminal stem structure, particularly adjacent to the central domain, might also contribute to inhibition of PKR (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although VA RNA I sequences from different virus serotypes vary considerably, all can be drawn in a similar extended structure consisting of three major domains (13,14) as follows: the terminal stem (including the paired 5Ј and 3Ј ends), a central domain, and the apical stem capped by a loop structure (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the nucleotide sequences of VA RNAs are poorly conserved between adenovirus serotypes, their secondary structure has been well maintained and can generally be divided into a terminal stem, a panhandle apical stem, and a more structured central domain ( Fig. 1) (15,32,36). Mutagenic studies indicate that the apical stem-loop is required for binding to PKR and that the central domain is involved in the inhibition of PKR activation (35)(36)(37).…”
mentioning
confidence: 99%
“…1) (15,32,36). Mutagenic studies indicate that the apical stem-loop is required for binding to PKR and that the central domain is involved in the inhibition of PKR activation (35)(36)(37). The terminal stem is essential for binding to Exp 5, which mediates VA transport to the cytoplasm (16,17).…”
mentioning
confidence: 99%